Benzyl Isothiocyanate Induces Apoptosis and Inhibits Tumor Growth in Canine Mammary Carcinoma via Downregulation of the Cyclin B1/Cdk1 Pathway - Cheng, Nan; Diao, Hongxiu; Lin, Zhaoyan; Gao, Jiafeng; Zhao, Ying; Zhang, Weijiao; Wang, Qi; Lin, Jiahao; Zhang, Di; Jin, Yipeng; Bao, Yongping; Lin, Degui (Frontiers in Veterinary Science, 2020)
Background: Breast cancer is common in female dogs and its poor prognosis remains a big clinical challenge, especially in developing counties. Benzyl isothiocyanate (BITC) has been attracted great interests due to its effect to inhibit tumor activities. However, little is known on its effect and mechanisms of action in canine mammary cancer. In this present study, BITC has been shown to suppress mammary tumor growth both in vivo and in vitro and some of potential mechanisms are revealed. Methods: The effect of BITC on canine mammary cancer was evaluated on CIPp and CMT-7364, canine breast cancer lines. The cell lines were treated with BITC and then tested using wound healing and invasion assays. Cell cycles and apoptosis were measured using flow cytometry, TUNEL assay, IHC, H＆E stained and/or qPCR. Results: BITC showed a strong suppression on both CIPp and CMT-7364 cells by inhibiting cell growth in vitro and the effects are both dose- and time-dependent. BITC also inhibited migration and invasion of CIPp and CMT-7364 cells. BITC induced G2 arrest and apoptosis, decreasing tumor growth in nude mice by down-regulation of cyclin B1 and Cdk1 expression. Conclusion: BITC suppressed growth of canine mammary tumor via down-regulation of cyclin B1/Cdk1 pathway.